Perancangan Sistem PPIC pada Perusahaan Seprai X - Gilbert Kelvin Widarta; Tanti Octavia; I Gede Agus Widyadana (Jurnal Titra, 2021)
This final project is done to design a Production Planning and Inventory Control system (PPIC) system for Bed Sheet X company. Currently, Bed Sheet X company does not have yet a PPIC system. Company is produced the products only to fulfill their maximum stock. The design of the PPIC system in this final project includes forecasting, designing Master Production Schedule (MPS) and Material Requirment Planning (MRP), and calculating lot sizing. Some forecast methods are compared in term of Mean Absolute Deviation (MAD) value. The Winter's Multiplicative method is the best method for each type of fabric. The Winter’s Multiplicative MAD value is 71.875. The lot sizing method used is Wagner Whitin Algorithm (WWA). The total cost of raw materials’ procurement is Rp. 34,968,493. After designing the PPIC system, a Visual Basic Application (VBA) is made to make it easier for users to do a production planning.